Decision support systems for urban water scarcity: Gaps, barriers and pathways to integrate nature-based solutions - A systematic review - Shahid Ali; Joaquim Comas; Ignasi Rodriguez-Roda (Environmental Modelling & Software, 2026)

Occurrence of Organic Micropollutants in the Water Cycle of a Euro-Mediterranean Resort: A Case Study - Lucia Gusmaroli; Josephine Vosse; Esther Mendoza; Ignasi Rodriguez-Roda; Giuliana Ferrero; Gianluigi Buttiglieri (Water, Air, & Soil Pollution, 2026)
Tourism can affect the availability and quality of freshwater resources, particularly in coastal regions like the Mediterranean. Water reuse is an increasingly adopted practice aimed at enhancing water resilience. To reduce pressure on freshwater resources, it is also being implemented in tourism-intensive areas at both centralised and decentralised scales. As a result, its potential environmental and public health risks are increasingly being investigated. At present, very few studies reported on the occurrence of organic micropollutants (OMP) in closed water cycles related to tourism, and to the best of the authors’ knowledge, only one of them differentiated their occurrence in the different water and wastewater streams. This article investigates the occurrence of a set of OMP in the water cycle of a large resort located in Lloret de Mar, Spain. It hereby considers tap and pool water, the separate greywater streams (kitchen, laundry, and bathroom greywater, where part of the greywater is reused for toilet flushing), and wastewater. The target compounds include 39 OMP: 10 endocrine disruptors and related compounds (EDCs) and 29 pharmaceuticals (PhACs), most of them scarcely studied in the context of tourism in most investigated matrices, especially greywater, and some here reported for the first time. Two sampling campaigns were performed in the high and low tourist seasons. OMP were ubiquitous, with the lowest total concentrations found in tap water, as expected (124 ng/L), and the highest, amounting to 315 μg/L, in wastewater in the low season. Kitchen greywater, one of the least previously studied matrices, resulted in the highest total EDCs concentration. The highest total concentration of PhACs, 185 μg/L, was found in wastewater in the low season. Daily per capita OMP loads in wastewater and greywater are also provided, proving the variability of loads in the wastewater streams of the same facility between seasons, contributing to a more differentiated understanding about their quality and impact on the total wastewater load.

Single-pass forward osmosis for efficient feed concentration: Optimizing multiple modules arrangement and flow distribution - Rajashree Yalamanchili; Pere Olives Cegarra; Albert Galizia; Ignasi Rodriguez-Roda; Gaëtan Blandin (Desalination, 2025)

Optimization of MBRs through integrated modelling: A state of the art - Giorgio Mannina; Marion Alliet; Christoph Brepols; Joaquim Comas; Marc Heran; Angel Robles; Ignasi Rodriguez-Roda; María Victoria Ruano; Valeria Sandoval Garcia; Ilse Smets; Jérôme Harmand (Journal of Environmental Management, 2024)

Can a forward osmosis-reverse osmosis hybrid system achieve 90 % wastewater recovery and desalination energy below 1 kWh/m3? A design and simulation study - Rajashree Yalamanchili; Ignasi Rodriguez-Roda; Albert Galizia; Gaëtan Blandin (Desalination, 2024)

Biological processes modelling for MBR systems: A review of the state-of-the-art focusing on SMP and EPS - Giorgio Mannina; Bing-Jie Ni; Jacek Makinia; Jérôme Harmand; Marion Alliet; Christoph Brepols; M. Victoria Ruano; Angel Robles; Marc Heran; Hazal Gulhan; Ignasi Rodriguez-Roda; Joaquim Comas (Water Research, 2023)